Pregnancy: an immune challenge - Maria Angelica Ehara Watanabe; Ellen Cristine Duarte-Garcia; Giovana Gomes de Carvalho; Natália Kimie Matsubara; Ana Camila Vaitkevicius Ferreira; Nágela Ghabdan Zanluqui; Gabriela Gonçalves de Oliveira (Semina: Ciências Biológicas e da Saúde, 2014)
Several studies demonstrate the importance of immunological aspects of pregnancy. During pregnancy, the embryo is implanted in the womb, where it will develop until the end of pregnancy. Amongst the immune aspects, the importance of the modulation of T lymphocytes, natural killers (NK) cells and many cytokines in maternal organism can be mentioned. The maternal tolerance to the fetus appears to be mediated by specific maternal hormones and by the expression of human leukocyte antigen G (HLA-G) - characteristic in pregnancy. Other studies suggest that fetal rejection and complications during pregnancy may occur because of the presence of minor histocompatibility antigens (mHAg), acquired by blood sharing of the mother with the fetus, and because of the presence of maternal antibodies against the sperm and against the fetus. The purpose of this review is to describe the immunological aspects that allow maternal tolerance to the fetus during pregnancy, as well as possible causes for rejection of the embryo and complications during pregnancy.